ESSENTIAL OIL COMPOSITION OF YARROW SPECIES (ACHILLEA MILLEFOLIUM L. AND ACHILLEA WILHELMSII L.): ANTIOXIDANT AND ANTIBACTERIAL ACTIVITIES OF ESSENTIAL OILS - YILDIRIM, Bunyamin; EKICI, Kamil; KOCAK, Mehmet Zeki (Studia Universitatis Babeș-Bolyai Chemia, 2023)
Of the medicinal plants’ cosmos, yarrow species (A. millefolium L. and A. wilhelmsii L.) are of the reputed species due to their phytochemical composition and thereby antioxidant and antibacterial activities. Owing to the high diversity in chemical composition and production of essential oil, the species deserves to be investigated more. In this context, wild yarrow plants were collected in Eastern Anatolia region (Van, Türkiye) and then the dried samples of the plants were subjected to hyd-rodistillation for essential oil extraction. In addition, the essential oils were assayed for their potential antioxidant and antibacterial activities. Gas Chromatography Mass Spectrometry (GC-MS) analysis revealed the presence of 1,8-cineole (75.19%), α-phellandrene (5.53%), P-eugenol (5.53%), camphor (5.45%), α-terpineol (2.09%), β-pinene (1.66%), camphene (1.20%), α-pinene(1.02%) from A. millefolium L. However, A. wilhelmsii was characterized with menthoglycol (35.84%), 1,8-cineole (34.04%), endo-borneol (9.93%), chrysanthenil acetate (4.76%), thymine (3.66%), terpinene-4-ol (2.33%), camphene (1.66%), and verbenole (1.53%). Regarding scavenging activities of the species, A. wilhelmsii exhibited better activity than A. millefolium, with a value of 6.5 mM and 4.2 mM Trolox equivalents (TEAC) respectively. With respect to the antibacterial activity against three gram-negative and three gram-positive bacteria, essential oils of both species were compared with standard antibiotic discs (ampicillin and ofloxacin).